Indoor air quality and the resident's health complaints after eruption of Mount Sinabung, Indonesia - Tarigan, Yenni Gustiani; Ferusgel, Agnes; Kachingwe, Baxter Hepburn Kayinga (Universitas Nahdlatul Ulama Surabaya, 2022)
The purpose of this study was to measure the concentration of exposure to indoor particulate matter (PM1, PM2.5, PM10), CO2, RH, and temperature and to evaluate public health complaints due to volcanic ash after the eruption of Mount Sinabung. A correlation analytic was assessed with a cross sectional approach at Payung, Gurukinayan and Perbesi villages from April to July 2021. The level of particles (PM1, PM2.5, PM10), CO2, temperature and humidity were measured by the AS-LUNG type 0019 instrument, Academia Sinica, Taiwan. Respondents' health complaints were evaluated by interviewing respondents using questionnaires. The Mann Whitney U test was used to analyze the differences levels of particles in the area zone. Multivariate analysis of covariance (MANCOVA) was used to evaluate the effect between the concentrations of particulate matter exposure on respondents’ health complaints. The results showed that the mean concentration of exposure to PM1, PM2.5, PM10 in Perbesi and Gurukinayan villages was above maximum level required by Indonesia indoor air quality guideline No. 1077 while CO2 was still below the maximum level required. According bivariate test, there was a significant difference in particle concentration between three villages (p-value = 0.00) and in particle concentration between area zone (p-value = 0.00). The MANCOVA test showed that exposure to PM1, PM2.5, PM10, CO2, RH, and temperature has an effect on eye complaints (p-value <0.05), exposure to PM1, PM2.5, PM10, and RH (p-value <0.05) has an effect on respiratory complaints, and exposure to PM10 (p-value <0.05) has an effect on skin diseases.